The Effect of Education on Visual Inspection With Acetic Acid (VIA) Through Interactive Video on The Behavior of Women of Reproductive Age in The Working Area of Talise Health Center - Irmayanti; Nur, Rosmala; Rahman, Abd; Fauzan, Fauzan; Devi, Ratna (Rifa'Institute, 2025)
Introduction: VIA screening coverage in Palu City, especially at Talise Health Center, remains low at 6.75%, far below the 90% national target. In 2023, 209 women were screened (3 positive), increasing to 238 in 2024 (14 positive). Objective: To assess the effect of interactive video based VIA education on the behavior of women of reproductive age. Method: A quantitative quasi-experimental study involving 99 respondents selected through proportionate stratified random sampling. Data were analyzed using univariate methods and One Way ANOVA. Results and Discussion: The knowledge variable showed significant differences between groups (F=103.638; p=0.000), with the highest improvement in the interactive video group. The attitude variable also showed significant differences (F=167.219; p=0.000), with interactive video producing the best results. The practice variable showed significant differences (F=206.243; p=0.000), with interactive video having the strongest effect on improving IVA screening practices. Conclusion: Therefore, education using interactive videos proved to be more effective in increasing knowledge, shaping positive attitudes, and encouraging actual screening behavior among WRA.